Non-Tariff Measures and Competitiveness of Indonesia’s Natural Rubber Export in Destination Countries - Prasada, Imade Yoga; Dhamira, Aura (AGRARIS: Journal of Agribusiness and Rural Development Research, 2022)
In the last few decades, the implementation of tariff policies between countries has declined. As a result, the enforcement of non-tariff measures (NTMs) experiences an increase. Implementing NTMs raises a new obstacle to trade activities in the global market, including the trade of Indonesia’s natural rubber. Therefore, this study was conducted to determine the effect of enforcing NTMs on the export competitiveness of Indonesia’s natural rubber. This study utilized secondary data from UN COMTRADE on 1995 to 2019. The data was analyzed using frequency index, coverage ratio, comparative advantage, and two-stage least square regression model. The results revealed that India, China, and the USA enforced the most NTMs of Indonesia’s natural rubber. Additionally, the implementation of NTMs in importing countries positively correlated to the export competitiveness of Indonesia’s natural rubber in destination countries.